2011
DOI: 10.1080/08995605.2011.570583
|View full text |Cite
|
Sign up to set email alerts
|

Military Personality Research: A Meta-Analysis of the Self Description Inventory

Abstract: The generalizability of personality-outcome relationships in military settings, argued to be a strong situation in the present research, was examined using metaanalysis. Effects based on the Self Description Inventory (SDI) gathered from 20 independent military samples (k = 117, total N = 34,217) were analyzed. Overall, findings concerning conscientiousness and neuroticism provide evidence for the validity of personality in military samples. However, a few constrained associations (e.g., openness-training perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
(54 reference statements)
3
24
0
Order By: Relevance
“…O' Keefe (1998) found that Neuroticism (and no other Big Five factor) of the TSD was related to performance in NCM basic recruiting training (r = −.40). This finding is consistent with Barrick et al's (2001) meta-analysis that reported that Neuroticism had a significant and negative association with teamwork, and with the literature that associates Neuroticism with anxiety, depression, irritability, and ability to perform effectively in a stressful environment (see Darr, 2011). Darr's (2011) meta-analysis of the TSD found that Neuroticism and Conscientiousness had a significant association with NCM training performance.…”
Section: Study 3: Criterion-related Validation Using Basic Training Rsupporting
confidence: 89%
See 3 more Smart Citations
“…O' Keefe (1998) found that Neuroticism (and no other Big Five factor) of the TSD was related to performance in NCM basic recruiting training (r = −.40). This finding is consistent with Barrick et al's (2001) meta-analysis that reported that Neuroticism had a significant and negative association with teamwork, and with the literature that associates Neuroticism with anxiety, depression, irritability, and ability to perform effectively in a stressful environment (see Darr, 2011). Darr's (2011) meta-analysis of the TSD found that Neuroticism and Conscientiousness had a significant association with NCM training performance.…”
Section: Study 3: Criterion-related Validation Using Basic Training Rsupporting
confidence: 89%
“…Although the correlation coefficients were lower than those reported by O'Keefe (1998; r = −.41), they are similar to Darr's (2011) meta-analysis (r = −.12) and suggest that Neuroticism is useful in distinguishing between success and failure in basic military training. Moreover, the 15-and 20-item TSD were psychometrically sound and were as good as the 75-item TSD-PI in determining between success and failure in BRT.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This test produced scores for conscientiousness and emotional stability that were used to test our hypotheses, as well as scores on agreeableness, extraversion, and openness to experience to allow for more exploratory analyses. The five‐factor structure of the instrument has been supported in an analysis of 66,982 officer applicants, with coefficient alphas for Big Five factor scores ranging from .89 to .97 (Manley, ), and the SDI Big Five scale content has been well‐validated as a predictor of job and training performance across many contexts (meta‐analysis: Darr, ). Test–retest reliability estimates of the SDI+ scores are presented in Table .…”
Section: Methodsmentioning
confidence: 98%